Factors predictive of lymph node metastasis in the follicular variant of papillary thyroid carcinoma. Issue 10 (12th August 2013) - Blanchard, C.; Brient, C.; Volteau, C.; Sebag, F.; Roy, M.; Drui, D.; Hamy, A.; Mathonnet, M.; Henry, J.‐F.; Mirallié, E.
Abstract : Background: The treatment of papillary thyroid carcinomas larger than 1 cm usually consists of total thyroidectomy and central lymph node dissection (LND). In patients with the follicular variant of papillary thyroid carcinoma (FVPTC), preoperative cytology and intraoperative frozen‐section analysis cannot always establish the diagnosis. The aim of this study was to evaluate predictive factors for lymph node metastasis in patients with FVPTC and to identify patients who might benefit from LND . Methods: The study included patients with FVPTC treated by total thyroidectomy and LND between 2000 and 2010 in four departments. When fewer than six non‐involved lymph nodes were removed, the patient was excluded from the analysis . Results: Some 199 patients were included. The median tumour size was 17 (range 1–85) mm, and tumours were classified as T1a in 28 patients, T1b in 40, T2 in 53, and T3 in 78. Eighty‐one patients (40·7 per cent) had lymph node metastasis (51 classified as N1a and 30 as N1b). Four risk factors were predictive of lymph node metastasis in the multivariable analysis: multifocality (odds ratio (OR) 2·36, 95 per cent confidence interval 1·15 to 4·86), angiolymphatic invasion (OR 3·67, 1·01 to 13·36), absence of tumour capsule (OR 3·00, 1·47 to 6·14) and tumour involvement of perithyroid tissue (OR 3·89, 1·85 to 8·18). The rate of lymph node metastasis varied between 14 and 94 per cent depending on the presence of risk factors . Conclusion: The rate of lymph node metastasis in patients with FVPTC varies widely according to the presence or absence of predictive risk factors . Abstract : Lymph node dissection could be omitted in many patients